Why Are So Many Nepali Women Killing Themselves? A Review Of Key Issues - Simkhada, P; Van Teijlingen, E; Winter, R C; Fanning, C; Dhungel, A; Marahatta, S B (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
For decades the maternal mortality in Nepal was the lead cause of death among women, with serious improvements in the maternal mortality ratio in the twentieth century the second most common cause has become more prominent. Suicide is now one of the leading causes of death for women of a reproductive age in Nepal. This scoping review brings together the key available literature to identify the causes of suicide among women in Nepal. Published and unpublished studies and the grey literature published on women and suicide related to Nepal between 2000 and 2014 were searched and included in this review. This review suggested a number of explanations for high rate of suicide among women including: partner violence, alcoholism and polygamy, the culture of silence, early age marriage and prolonged child bearing and dependency on men for financial security. This paper highlights some challenges and suggests ways forward in the improvement of mental health in Nepal. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.12001 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 Page: 43-49